Tungstophosphoric acid and zirconia supported on mesoporous silica catalyst in veratrole acetylation - Halligudi, Shivaraj B. (From ZEOLITES to Porous Mof Materials: The 40th Anniversary of International ZEOLITE Conference, Proceedings of The 15th International ZEOLITE Conference, 2007)
Tungstophosphoric acid (TPA) over zirconia dispersed uniformly in mesoporous silica (MS) channels of MCM-41 and MCM-48 was synthesised and tested for its catalytic activity in veratrole acetylation. Catalysts with different TPA loadings (5 to 50 wt.%) on 22.4 wt.% ZrO(2)/MCM-41 and 15 wt.% TPA on different zirconia loadings (10-70 wt.%)/MCM-41 were prepared and calcined at 1123 K. Catalysts were characterised by known techniques. Mesoporous silica supports play an important role in stabilising catalytically active TPA along with tetragonal phase of zirconia. Among the catalysts, 15 wt.% TPA/22.4 wt.% ZrO(2)/MCM-41 calcined at 1123 K was found to have the highest acidity and be at least four times more active than neat 15 wt.% TPA/ZrO(2) in veratrole acetylation to acetoveratrone by acetic anhydride.
15th International Zeolite Conference, Beijing, PEOPLES R CHINA, AUG 12-17, 2007